Robert Adamson reading his poetry and being interviewed by Rodney Hall in the Poets on record collection - Adamson, Robert, 1943-2022; Hall, Rodney, 1935-; University of Queensland. Press (1973)
This is part of a collection of interviews with Australian poets introducing themselves and reading selections from their own poetry.
Recording begins on Tape 30, side 1, cut 2 and finishes on Tape 31, side 2, cut 1.
Digital master available
Keywords: Adamson, Robert, -- 1943- -- Interviews; Poets, Australian -- 20th century; Australian poetry -- 20th century; Oral interpretation of poetry